PEMANAS INDUKSI UNTUK BALL BEARING DIAMETER NOMINAL 15,17, DAN 20 MM - Febriyan Azril Mohamad; Dista Yoel Tadeus; Fakhruddin Mangkusasmito; Ari Bawono Putranto (BERKALA FISIKA, 2023)
Bearing is an important component in supporting engine performance. However, according to a study  by  Svenska  Kullager  Fabriken  (SKF),  bearings  are  also  one  of  the  components  that  most often cause 40% of engine damage. Bearing damage occurs during installation which is still done manually, namely being hit which results in high friction on the wheel axles. To overcome this, a tool is made with the heating method to carry out bearing installation which utilizes expansion of the  bearing.  Induction  heating  device,  is  a  solution  for  heating  bearings  which  has  not  been produced in Indonesia. Therefore, an induction heating system was created for heating bearings using the NodeMCU ESP8266 microcontroller as a controller and using a type k thermocouple temperature sensor as a temperature detector with the PID method. The use of this PID method as a  heating  temperature  control  when  it  reaches  the  desired  set  point,  the  heating  process  will automatically stop. The objects used are bearings with inner rings of 15mm, 17mm and 20mm. By making this induction heater, the performance of the tool is obtained with an average heating time to reach a set point temperature of 100OC is 3.64 minutes.